African Development Indicators 2002 : Drawn from the World Bank Africa Database - Badr, Ziad (Africa Development Indicators, 2002)
This volume presents data from 53 African countries, arranged in separate tables or matrices for more than 500 development indicators. The indicators are grouped into 14 chapters: background data, national accounts, prices and exchange rates, money and banking, the external sector, external debt and related flows, government finance, agriculture, power, communications and transportation, public enterprises, labor force and employment, aid flows, social indicators, and environmental indicators. Each chapter begins with a brief introduction on the nature of the data and their limitations, followed by a set of charts, statistical tables, and technical notes that define the indicators and identify their specific source. Most of the indicators present data by year for the period 1970-99. Many indicators also include averages or average growth rates for three recent time periods, covering the years 1975-99 or the most recently available year. Efforts have been made to standardize the data to facilitate cross-country comparisons. The data in this book are derived from a variety of sources. In most cases, the original sources are the national statistical services in Africa. In addition, many international agencies collect or compile data on African countries and organize national data in a standardized framework. The data have been supplemented by World Bank staff estimates to help address problems of missing or inconsistent data from standard sources